1999
DOI: 10.1080/095530099140375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 915-MHz simulated mobile phone signal on cognitive function in man

Abstract: There was evidence of an increase in responsiveness, strongly in the analogue and less in the digital simulation, in choice reaction time. This could be associated with an effect on the angular gyrus that acts as an interface between the visual and speech centres and which lies directly under and on the same side as the antenna. Such an effect could be consistent with mild localized heating, or possibly a non-thermal response, which is nevertheless power-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
7
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(212 citation statements)
references
References 0 publications
12
186
7
7
Order By: Relevance
“…In particular, Preece et al [1999] and Koivisto et al [2000a,b] reported a shortening of the RT. Some work on verification of these reports failed to confirm their findings [Haarala et al, 2003.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, Preece et al [1999] and Koivisto et al [2000a,b] reported a shortening of the RT. Some work on verification of these reports failed to confirm their findings [Haarala et al, 2003.…”
Section: Discussionmentioning
confidence: 97%
“…Preece et al [1999] conducted tests on a variety of short-term and longterm memory tasks, and reaction time (RT) tests. The subjects were exposed to RFR at 915 MHz (1 and 0.25 W powers).…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy was employed to index possible biased responding. These tasks tested very basic information processing and were used to assess a variety of possible impacts on neural function, including acute mobile phone exposure [Preece et al, 1999]. .…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…They suggest the temperature rise from the 915 MHz MP at maximum power in the brain is well below the 1 8C rise in temperature where learning effects are known to occur. Preece et al [1999] examined whether a simulated MP transmission at 915 MHz has an effect on cognitive function in man. Thirty-six subjects, 21-60 years of age (two were left handed) in two groups, had three test sessions in a randomized three way cross-over design.…”
Section: Cognitive Studiesmentioning
confidence: 99%